IMPACT OF CO-OPERATIVE LOAN ON SMALL AND MARGINAL FARMERS OF E.G.DISTRICT OF ANDHRA PRADESH - R. UMA DEVI (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, ECONOMICS & MANAGEMENT, 2013)
Agriculture forms the backbone of the Indian economy. It contributes 18.5 percent to the GDP and provides employment to about 52 percent of the total working population during the year 2006-07. The advanced technological changes in the agricultural sector necessitated the requirement of more working capital. Hence, the poor peasants in India are in search of timely credit. Co-operative banks were established on the principle of co-operation and to serve the poor peasants. The main function of these banks is to relieve the poor farmers from the clutches of money lenders. These are playing significant role in extending credit to the farm sector besides providing inputs, marketing and extension services. Particularly in the state of Andhra Pradesh (A.P.), Co-operatives play a very important and crucial role in the growth and development of agricultural sector. East Godavari District is an agriculturally developed district in Andhra Pradesh where paddy forms up to 53 percent of the total cultivated area. In the district, Co-operatives are functioning in most efficient manner by providing adequate, cheap and timely credit to agriculture and allied sector. They spread to the remote areas of the district in order to serve the needy farmers. These Banks accept deposits and lend both short-term and long-term credit for production and investment purpose through Primary Agricultural Co-operative Societies (PACS) and also directly to the farmers. Co-operative Banks are the friendly banks developed to relieve the poor from the vicious circle of poverty.These areproviding timely and adequate credit to the three sectors viz., primary, secondary and territory, particularly to agriculture and allied sector at cheaper rates. On this backdrop, an attempt is made to analyze the impact of cooperative loans on the agricultural development of the state, Andhra Pradesh. In order to study the impact, East Godavari district is to be chosen as sample as it represents the overall characteristics of Andhra Pradesh.